2020
DOI: 10.1186/s12887-020-02071-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with radiosynoviorthesis in hemophilic patients with and without inhibitor

Abstract: Background: Spontaneous bleedings occurring into joints (hemarthrosis) are the most common manifestations of hemophilia and causes severe joint damage ultimately resulting in joint disfunction known as hemophilic arthropathy. Among available therapeutic options for reducing recurrent hemarthrosis-associated damage, radiosynoviorthesis (RS) has proven effective in improving joint function. Aim: To assess the impact of RS with Yttrium(90) citrate (C-Y(90)) on frequency of hemarthroses and joint function in a gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The result was underlined by the data from Peter et al 2005 10 and Tena et al who reported good to excellent results for radiosynovectomy in 60-80% of patient with hemarthrosis. 11 Similar result was found in the study by Martinez, who reported a significant decreased in bleeding frequency in 70-80% of patient. 12 Rate of bleeding frequency was the only variable used to determine treatment failure, hence the need of further radiosynovectomy.…”
Section: Therapy Response On Bleeding Frequencysupporting
confidence: 85%
“…The result was underlined by the data from Peter et al 2005 10 and Tena et al who reported good to excellent results for radiosynovectomy in 60-80% of patient with hemarthrosis. 11 Similar result was found in the study by Martinez, who reported a significant decreased in bleeding frequency in 70-80% of patient. 12 Rate of bleeding frequency was the only variable used to determine treatment failure, hence the need of further radiosynovectomy.…”
Section: Therapy Response On Bleeding Frequencysupporting
confidence: 85%
“…Forty‐three studies had sample sizes > 20 knees 5–47 . Sixty‐eight studies were defined as small and were not discussed further.…”
Section: Resultsmentioning
confidence: 99%
“…15,29,34 A greater magnitude of improvement was seen in the short term in a paediatric cohort from Mexico, though the degree of underlying arthropathy was unknown. 45 Muscle strength is infrequently reported as a functional outcome, however a 10% improvement has been reported with Y-90 using the Medical Research Council scale of muscle power. Improvement in ROM and muscle strength both occurred regardless of whether radiographic arthropathy was present or not.…”
Section: Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the procedure varies depending on the joint and the severity of the hemarthropathy. Two recent studies show that the dosage of coagulation factors needed decreases after RSO [ 75 , 76 ]. In the study by Kachooei et al, [ 188 Re]rhenium colloid was used, but similar results can be expected with the approved [ 186 Re]rhenium colloid.…”
Section: Indications For Radiosynoviorthesismentioning
confidence: 99%